Geochemical Study of the Formation Process for the Saline Lakes in the Dry Valleys, South Victoria Land, Antarctica - Shyu NAKAYA; Masakichi NISHIMURA (National Institute of Polar Research, 1977)
A simple model is proposed for the present chemical composition of the saline lakes in the Dry Valleys. A diluted water of sea salt whose compositional ratio was that of sea water was concentrated by evaporation to the present chlorinity. During the concentration process, a part of Na^+ and K^+ replaced Ca^ and Mg^ of the sediment or weathering rock, and some part of CaSO_4 deposited from the solution. All the reaction proceeded under an ionic massbalance. This simple idea can beautifully explain the origin of the chemical compositions of Lakes Vanda and Bonney. The salt concentration profiles in these saline lakes can be explained by the molecular diffusion (or ionic diffusion) of dissolved chemical substances from the bottom layer to the surface layer. The vertical transport of salt from the bottom layer is given by a conventional Fickian equation, with a diffusion coefficient (D); [numerical formula] where C is the salt concentration, z is the vertical distance coordinate increasing upward from z=0 at the bottom to z=h at the top of the saline layer, and t is time. For eq. (1), the initial and boundary conditions are [numerical formula] [numerical formula] [numerical formula] The solution of (1), obtained by the Laplace transformation with the boundary conditions (2)-(4) is [numerical formula] whereφ_1 is a function of time (t), height (z), and diffusion coefficient (D), its complete form being [numerical formula] The value of t of these saline lakes in the Dry Valleys is estimated by trial and error computation using eq. (5) and (5a). The age of stratification estimated for the salt diffusion from the bottom layers ranges from 1,000 to 1,250 years.